Dimethyl Sulfoxide Leads to Decreased Osteogenic Differentiation of Stem Cells Derived from Gingiva via Runx2 and Collagen I Expression - Lee, Hyunjin; Park, Jun-Beom (European Journal of Dentistry, 2019)
Objectives Dimethyl sulfoxide (DMSO) plays various functions, including cellular functions such as cellular growth. The aim of this study was to evaluate the effects of DMSO on the proliferation and osteogenic differentiation of human gingiva-derived stem cells.Materials and Methods Stem cells derived from gingiva were cultured in the presence of DMSO at concentrations ranging from 0.01 to 10%.Statistical Analysis We performed a one-way analysis of variance (ANOVA) with post hoc test to determine the differences between the groups using a commercially available program and the level of significance was 0.05.Results The cells in the control group showed normal fibroblast morphology. The cells treated with 0.01%, 0.01%, 0.1%, and 1% DMSO were morphologically similar to those from the control group on each day. Statistically significant decreases in cell counting kit-8 (CCK-8) values were seen in the 3% and 10% DMSO groups (p < 0.05). A statistically significant decrease in alkaline phosphatase activity was seen in the 3% DMSO group. (p < 0.05). The application of DMSO produced a decrease in alizarin red S staining. The expression of Runx2 and collagen I by immunofluorescence decreased as the dose of lovastatin increased.Conclusion The effects of DMSO on the viability of osteogenic differentiation among stem cells derived from human gingiva were evaluated. Applying DMSO produced decreased cell viability and decreased osteogenic differentiation in this experimental setting. This should be considered when designing and interpreting the data, and a DMSO-free method may be considered for bone regeneration applications.
Keywords: osteogenic differentiation; proliferation; dimethyl sulfoxide; gingiva; stem cells